Influence of Wafer Probing Against Initial Bonding - Suresh, Kumar; Sivarao, Subramonian; Guan, Tan Kim; Harun, Fuaida (2010)
Wafer probing technology is a critical testing technology used in the semiconductor manufacturing and packaging process. A well-designed probing system must enable low and stable contact resistance when each needle-like probe makes contact with the IC chip-bonding pad. During wafer testing, probe needles are brought in mechanical contact with aluminum bond pads and electrical contact is made as the probes "scrub" through the oxide and contaminants on the pad surface. This scrubbing action causes the probe needle to disturb or damage the pad metal. This scrub damage can adversely impact the wire bond quality at assembly and add extra costs by lowering bond and assembly yields. As the amount of pad damage increases, the strength and integrity of the bond is reduced. If the bond is too weak, the ball could potentially lift off the pad during the bond process at assembly. This effect is exacerbated for ultra fine pitch bond pads since a larger percentage of the total pad area is damaged during probe test. This paper will be evaluating on the different impacts of probe conditions to wire bondability based on both the probe and wafer technology. It was found that pad damage area has a direct impact to bond quality. The larger pad damage area the lower the bond quality and this depends on the factors like probe technology, number of probe touchdown, probe overdrive as well as optimal wire bonding parameters. Results showing that vertical probe technology are better than both advanced and standard cantilever technology while bonding quality can still be maintained even if the probe damage is large as long as bond location is at the toe and not at the center or the heel of the damage area.